2017
DOI: 10.3389/fphys.2017.00627
|View full text |Cite
|
Sign up to set email alerts
|

Nature's Electric Potential: A Systematic Review of the Role of Bioelectricity in Wound Healing and Regenerative Processes in Animals, Humans, and Plants

Abstract: Natural endogenous voltage gradients not only predict and correlate with growth and development but also drive wound healing and regeneration processes. This review summarizes the existing literature for the nature, sources, and transmission of information-bearing bioelectric signals involved in controlling wound healing and regeneration in animals, humans, and plants. It emerges that some bioelectric characteristics occur ubiquitously in a range of animal and plant species. However, the limits of similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 220 publications
(287 reference statements)
0
49
0
1
Order By: Relevance
“…Electrical processes also play important roles in morphogenesis; it has been demonstrated that endogenous voltage gradients drive wound healing in animals (including humans) and plants (14,15). The electrical processes in cells, even those that are not electrically excitable, seem to play a regulatory role and are integrated during embryogenesis with the biochemical signals (7,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Electrical processes also play important roles in morphogenesis; it has been demonstrated that endogenous voltage gradients drive wound healing in animals (including humans) and plants (14,15). The electrical processes in cells, even those that are not electrically excitable, seem to play a regulatory role and are integrated during embryogenesis with the biochemical signals (7,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The electrical processes in cells, even those that are not electrically excitable, seem to play a regulatory role and are integrated during embryogenesis with the biochemical signals (7,(16)(17)(18). The connection between bioelectric processes and other processes leading to cell proliferation, motility, and apoptosis in morphogenesis during development and cancer is beginning to be elucidated (7,14,19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Инвазивная установка электродов, сопряженная с повреждением тканей, может приводить к существенному изменению БЭП, которые в этой ситуации отражают не физиологические, а стрессовые процессы в организме [11]. Так, широко известные методы регистрации БЭП в теле человека -электрокардиография и электроэнцефалография, используемые для регистрации и исследования электрических процессов, протекающих при работе сердца и мозга, -базируются именно на установке неинвазивных электрических контактов.…”
unclassified